How to improve social media apps for online purchase behavior by Chinese young consumers generation y in order to influence the purchase of fresh food products from SMEs? - Le, Li; Zeng, Jian-Hua; Ismail, Noor Azlin; Choo, Wei Chong (Asian Scholars Network, 2023)
This study intends to analyze the factors that influence mobile customers of Generations Y repurchase intentions for agricultural fresh food product apps and Small and Medium-sized Enterprises (SMEs’) E-commerce fresh food platforms. Beginning with a rationale and background information of China's agricultural fresh food internet marketing and retail business.